The clash of ideas in world politics transnational networks, states, and regime change, 1510-2010 - Owen, John M. (John Malloy) 1962- (Princeton studies in international history and politics, 2010)
Some blame the violence and unrest in the Muslim world on Islam itself, arguing that the religion and its history is inherently bloody. Others blame the United States, arguing that American attempts to spread democracy by force have destabilized the region, and that these efforts are somehow radical or unique. Challenging these views, The Clash of Ideas in World Politics reveals how the Muslim world is in the throes of an ideological struggle that extends far beyond the Middle East, and how struggles like it have been a recurring feature of international relations since the dawn of the modern